Crystal structures of bis[1-(1-hydroxypropan-2-ylidene)thiosemicarbazide-κ3S,N,O)cobalt(III)-tetra(thiocyanato-κN) cobalt(II) methanol solvate, bis1-(1-hydroxypropan-2-ylidene)thiosemicarbazide-κ3S,N,Onickel(II) bis(thiocyanate) and (1-(1-hydroxypropan-2-ylidene)thiosemicarbazide-κ3S,N,O)bis(thiocyanato-κN)zinc(II) - Ndoye, Cheikh; Excoffier, Gregory; Seck, Gorgui Awa; Diouf, Ousmane; Thiam, IbraIbrahima Elhadji; Sidibe, Mamadou; Gaye, Mohamed (European Journal of Chemistry, 2022)
The reactions of Schiff base 1-(1-hydroxypropan-2-ylidene)thiosemicarbazide (H2L), with salt of thiocyanate metal (II) (Co, Ni, or Zn), provided one dinuclear and two new mononuclear complexes, formulated respectively as [Co(LH)2]2·[Co(NCS)4] ·2(MeOH) (1), [Ni(H2L)2]·[(NCS)2] (2) and [Zn(H2L)(NCS)2] (3). These compounds have been studied and characterized by elemental analysis, infrared, and ultraviolet-visible (UV-vis) spectroscopies. The structures of the three complexes have been resolved by X-ray crystallography technique. The dinuclear complex 1 crystallizes in the orthorhombic space group Fdd2 with the following unit cell parameters a = 33.1524 (3) Å, b = 19.3780 (2) Å, c = 13.2533 (2) Å, V = 8514.28 (17) Å3, Z = 16, R1 = 0.025 and wR2 = 0.063, the mononuclear complex 2 crystallizes in the monoclinic space group P21/n with the following unit cell parameters a = 11.5752 (1) Å, b = 12.3253 (1) Å, c = 14.2257 (2) Å, β = 106.855 (1)°, V = 1942 (4) Å3, Z = 4, R1 = 0.038 and wR2 = 0.106 and the mononuclear complex 3 crystallizes in the monoclinic space group P21/c with the following unit cell parameters a = 6.1121 (2) Å, b = 26.8272 (7) Å, c = 8.0292 (2) Å, β = 99.876 (3)°, V = 1297.04 (6) Å3, Z = 4, R1 = 0.026 and wR2 = 0.057. The asymmetric unit of Complex 1 contains one cationic unit in which the ligand acts in its monodeprotonated form in tridentate fashion and one half of the anionic unit containing two thiocyanate co-ligands. In complexes 2 and 3, the ligand acts in its neutral form in a tridentate manner. In complex 2, two ligand molecules coordinate the Ni(II) center, and the thiocyanate moieties remains uncoordinated. In complex 3, the Zn(II) is coordinated by one ligand molecule and two thiocyanate groups through their nitrogen atoms. Numerous hydrogen bonds consolidated the structures of complexes 1, 2, and 3 in a three-dimensional network.